Thermal Analysis of Solar Protection on Windows in Tropical Areas - Fadhilla Azherda; Remon Lapisa; Waskito Waskito; Hasanuddin Hasanuddin (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
Thermal comfort is one element of comfort that is very important, because it concerns the condition of the room temperature. Where the cool temperature in the room is a condition of thermal comfort of a building, besides indoor lighting also affects the comfort of the room. The building window is one of the factors that affects the thermal comfort of the building, therefore, it is necessary to find the solution for the heat absorption that occurs through the glass window not directly into the building. This research aims to analyze the solar protection on the windows of the building on the teropical climate, in the windows of paired Building solar protection (Solar Shading) that can be variated tilt angle. which uses a variation of tilt angles of 0 ° (-), 45 ° (/), and 90 ° (|) with the aim of obtaining indoor thermal comfort as well as indoor lighting. Kenyamanan termal merupakan salah satu unsur kenyamanan yang sangat penting, karena menyangkut kondisi suhu ruangan. Dimana temperature dalam ruangan yang sejuk adalah syarat kenyamanan termal suatu bangunan, selain itu pencahayaan dalam ruangan juga mempengaruhi kenyamana dalam ruangan. Jendela bangunan merupakan salah satu faktor yang mempengaruhi kenyamanan termal pada bangunan, Oleh karena itu perlu dicarikan solusi agar penyerapan panas yang terjadi melalui jendela kaca tidak lansung masuk kedalam bangunan. Penelitian ini bertujuan untuk menganalisis proteksi surya pada jendela bangunan pada iklim teropis, pada jendela bangunan dipasangkan proteksi surya (Solar Shading) yang dapat divariasikan sudut kemiringan. dimana menggunakan variasi sudut kemiringan 0˚(-), 45˚(/), dan 90˚(|) dengan tujuan mendapatkan kenyamanan termal dalam ruangan dan juga pencahayaan dalam ruangan.